초등학생 구강보건교육을 위한 컴퓨터 기반 교육 프로그램 개발 및 효과 평가 - 문원숙; Won Suk Mun; 황태윤; Tae Yoon Hwang; 이경수; Kyeong Soo Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2014)
Objectives : The purpose of the study is to develop and to evaluate the oral health education program using computer assisted instruction(CAI) for the elementary school students. This study was carried out from November, 2012 to February, 2013. Methods : The subjects were 188 elementary school students of the first, second, and third grades in Buk-gu, Busan. The education was provided as computer assisted instruction and conventional classroom education. Three trained dental hygienists recorded three times of knowledge of oral health, oral health attitude, oral health behaviors and the plaque control index(O`Leary index). Results : CAI group showed high score of oral health knowledge of 6.74 points, 8.62 points and 8.38 points(p<0.01). In oral health attitude, the scores were 7.40 points, 8.01 points, and 7.99 points(p<0.05). In oral health behavior, the scores were 5.47 points, 6.14 points, and 5.61 points(p<0.05). The plaque control index was 22.59 points, 19.69 points, and 21.44 points(p<0.01). Conclusions : CAI education program of this study showed the effective education for the elementary school students. So the CAI education program can be useful and disseminated to the community project.